The Risk of Abortion and Stillbirth in Antithrombin-, Protein C-, and Protein S-deficient Women - Jan Sanson, Bernd; Friedrich, Philip W; Simioni, Paolo; Zanardi, Sandra; Huisman, Menno V; Girolami, Antonio; Wouter ten Cate, Jan; Prins, Martin H (Thrombosis and Haemostasis, 1996)
Hereditary deficiencies of the naturally occurring anticoagulants are well recognized conditions predisposing to recurrent venous thromboembolism. Since thrombotic phenomena have been implied as a cause of abortion and stillbirth, we hypothesized that these deficiencies increase the risk of fetal demise.A group of 129 female subjects who had been pregnant at least once and who had a family member with documented venous thrombosis associated with a deficiency of AT, PC or PS were studied. We first assessed the obstetric history and subsequently determined the deficiency status. In the 60 deficient subjects 42 (22.3%) of the 188 pregnancies resulted in miscarriage or stillbirth as compared to 23 (11.4%) of the 202 pregnancies in the 69 non-deficient subjects. The relative risk of abortion and stillbirth per pregnancy for deficient women as compared to non-deficient women was 2.0 (95% C.I. 1.2-3.3).